Promotion: Branding tool for Macedonia as a tourist destination - Violeta Milenkovska; Zoran Strezovski; Angela Milenkovska (UTMS Journal of Economics, 2015)
In times when competition between countries in the world is stronger, in order to attract as many tourists as possible, and strengthening their brand as a tourist destination, Republic of Macedonia started to build and strengthen its tourism brand. Due to the enormous competition, traditional destinations maintain and improve their brand through new innovative tourist attractions. On the contrary, the new tourist destinations strongly attack potential tourists with intention of gaining a better position on the tourist market. The subject of this paper is Macedonia as a tourist destination seen through the prism of promotional activities that Agency for promotion and support tourism in Republic of Macedonia realized in period 2009-2012. This paper presents an action research conducted on a sample of 65 tourist stockholders (travel agencies and hotels) in Macedonia in 2012. In this study it will be analyzed what other countries have undertaken regarding the aspect of promotion of their tourist product, concerning promotion of their tourist destination and what Macedonia has undertaken and should undertake regarding that aspect.
Keywords: M31; 330; agency for promotion; brand; Macedonia; activities; strategic position